2018
DOI: 10.1111/nuf.12295
|View full text |Cite
|
Sign up to set email alerts
|

Health policy engagement among graduate nursing students in the United States

Abstract: Health policy and advocacy education are important aspects of graduate nursing curriculum and have been integrated into curricula. Graduate nursing students at all levels reported that health policy AACN Essential competencies are being included in their program, either as stand-alone health policy courses or integrated health policy learning activities during matriculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…AACN established a Faculty Policy Think Tank (FPTT) to develop recommendations for improving nursing students at all levels and nurses' engagement in health care policy and those recommendations were published in 2017 [17]. De Cordova et al [18]. also suggested that more research on how health care policy courses were delivered should be conducted to impact future health care policy and advocacy efforts, even though there were already some health care policy courses included into nursing curricula in the U.S. Luo et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…AACN established a Faculty Policy Think Tank (FPTT) to develop recommendations for improving nursing students at all levels and nurses' engagement in health care policy and those recommendations were published in 2017 [17]. De Cordova et al [18]. also suggested that more research on how health care policy courses were delivered should be conducted to impact future health care policy and advocacy efforts, even though there were already some health care policy courses included into nursing curricula in the U.S. Luo et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing practice in all aspects is regulated by healthcare policies and is influenced by related changes [ 92 ]. The promotion of public health is considered the ultimate goal of health policies [ 93 ].…”
Section: Directives To Improve Nurses’ Job Conditions and Securitymentioning
confidence: 99%
“…Another way nursing educators can respond is through policy education. The American Association of Colleges of Nursing essentials require the inclusion of policy education and competencies in nursing curricula at the graduate level, 21 but research suggests policy education in nursing curricula does not result in policy engagement among graduate nursing students 22 . Future education research could identify best practices for integrating policy content across the nursing continuum, and action steps for translating education to action.…”
Section: Creative Conversationsmentioning
confidence: 99%